2022
DOI: 10.1007/s40290-022-00444-w
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Polyphenolic Flavonoids as Senotherapeutic Agents in Degenerative Diseases and Geroprotection

Abstract: Cellular senescence, a hallmark of ageing, contributes to tissue or organ dysfunction and the pathophysiology of diverse age-related diseases (ARD) by various mechanisms. Targeting it by selective elimination of senescent cells (SCs) or blocking senescence-associated secretory phenotypes (SASP) with natural or synthetic compounds has been suggested to improve lifespan. Dietary phytochemicals possess a broad spectrum of biochemical and pharmacological effects that are beneficial to human health. Flavonoids, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 173 publications
0
25
0
Order By: Relevance
“…It has a remarkable potential to selectively induce apoptosis (cell death) in senescent cells while leaving healthy cells unaffected [5]. Research has shown that FIS is considered one of the most potent senolytic compounds, exhibiting strong anti-senescence effects in preclinical studies across different tissues and animal models [6][7][8]. Its unique ability to promote the clearance of senescent cells has sparked interest in exploring FIS's therapeutic applications for extending health span and potentially addressing age-related ailments [9].…”
Section: Introductionmentioning
confidence: 99%
“…It has a remarkable potential to selectively induce apoptosis (cell death) in senescent cells while leaving healthy cells unaffected [5]. Research has shown that FIS is considered one of the most potent senolytic compounds, exhibiting strong anti-senescence effects in preclinical studies across different tissues and animal models [6][7][8]. Its unique ability to promote the clearance of senescent cells has sparked interest in exploring FIS's therapeutic applications for extending health span and potentially addressing age-related ailments [9].…”
Section: Introductionmentioning
confidence: 99%
“…These two cholesterol oxidative derivatives, mainly formed by cholesterol autoxidation, were identified at enhanced levels in the plasma of sarcopenic patients (Ghzaiel et al, 2021), and are often increased in patients with age-related diseases (Zarrouk et al, 2014) , A nutraceutical approach to the treatment of age-related diseases, including sarcopenia, has been favored for several years by our team and it is this guideline that led us to have an interest in PRPE. In addition, several polyphenols present in PRPE, such as resveratrol and quercetin, are now recognized for their senolytic properties which are attractive to fight aging and age-related diseases (Mbara et al, 2022). This aspect constituted an additional reason which motivated the evaluation of the cytoprotective and antioxidant activities of PRPE on AAPH-treated C2C12 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Among other agents presented in Table 1, the following also merit a mention. Luteolin plays a significant role as an antioxidant, antiinflammatory, and anticancer agent, scavenging free radicals and suppressing neuroinflammation (Mbara et al, 2022;Shi et al, 2004).…”
Section: Other Polyphenolsmentioning
confidence: 99%